Restoring Fiscal Discipline for Poverty Reduction in Peru : a Public Expenditure Review. (World Bank country study., 2003)
The purpose of this report is to provide diagnoses and policy recommendation in public expenditure management in Peru. The introductory chapter of the book provides a synthesis of Peru's public expenditure reform agenda from the Bank's perspective. Chapter II-IV examine the core functions of the public expenditure management. Chapters V-VIII explore selected themes such as the decentralization of public administration and the social sectors; civil service reform; governance and corruption; and mining and fiscal environmental issues.; The report does not attempt to provide full coverage of all areas affected by public expenditure. The book deliberately focuses on social sectors spending and leaves aside infrastructure and other sectors that have been the subject for more specific sector studies in previous years.